The State of Anthropological Uncertainty as an Educational Problem - Miczka, Tadeusz (European Journal of Multidisciplinary Studies, 2018)
The assumption was made that in the epoch defined as technopoly or techno-everydayness, in which almost every person is physically or mentally supported by technology, or is simply "improved" with the help of it (so-called Human enhancement), the sense of anthropological uncertainty appears to be more and more common. This was often emphasized by Jean Baudrillard, the author of the concept of the "disappearance of reality", proclaiming that the real world is replaced by simulacra: “Am I finally a human or a machine?” - he was asking and then answering in the following way – “Today the answer to this question no longer exists: I am a human being in real and subjective terms, but virtually and from a practical point of view I am a machine ". Even if his position is considered too radical, one cannot ignore or diminish the importance of the impact of high technology on the physical, and especially the mental condition of the users of everyday media. These considerations have focused on the educational implications of this impact, recognizing that young internet and smartphones users are more exposed to the effects of a sense of anthropological uncertainty than adults, and hence they require strong support in this area from pedagogical theories, and above all from pedagogical practices. Presentation of the current research findings in this area creates an opportunity to define the scope and program of modern media education, which has been called education for information freedom and information activism. Such a pedagogical concept is based on popularizing, teaching and shaping a positive attitude of young people towards the Internet and technological gadgets, which is based on the conscious observance of the principles of "information hygiene", and the supreme principle in this case is self-limitation. That is why the state of anthropological uncertainty is one of the most difficult challenges imposed by techno-everydayness that school and non-school education has to accustom with.
Keywords: Realignment of Education, Anthropological Uncertainty, Human Enhancement, Computer Addiction